FR‐190997, a Nonpeptide Bradykinin B2‐Receptor Partial Agonist, is a Potent and Efficacious Intraocular Pressure Lowering Agent in Ocular Hypertensive Cynomolgus Monkeys. Issue 4 (2nd May 2014) - Sharif, Najam A.; Katoli, Parvaneh; Scott, Daniel; Li, Linya; Kelly, Curtis; Xu, Shouxi; Husain, Shahid; Toris, Carol; Crosson, Craig
Abstract <table-wrap position="anchor" orientation="portrait"> Preclinical Research </table-wrap> FR‐190997 (8‐[2, 6‐dichloro‐3‐[N‐[(E)‐4‐(N‐methylcarbamoyl) cinnaminoacetyl]‐N‐methylamino]benzyloxy]‐2‐methyl‐4‐ (2‐pyridylmethoxy) quinoline), a nonpeptide bradykinin (BK) B2‐receptor‐selective agonist, represents a novel class of ocular hypotensive agents. FR‐190997 exhibited a high affinity for the human cloned B2‐receptor (Ki = 9.8 nM) and a relatively high potency (EC50 = 155 nM) for mobilizing intracellular Ca2+ ([Ca2+]i) in human ocular cells from nonpigmented ciliary epithelium; trabecular meshwork [h‐TM]; ciliary muscle [h‐CM] that are involved in regulating intraocular pressure (IOP). Unlike BK, FR‐190997 behaved as a partial agonist (Emax = 38–80%) in these cells and its [Ca2+]i — mobilizing effects were blocked by the B2‐receptor‐selective antagonists (HOE‐140, Ki = 0.8–7 nM; WIN‐64338, Ki = 157–425 nM). FR‐190997 stimulated the production of prostaglandins (PGs) in h‐CM and h‐TM cells (EC50 = 15–19 nM; Emax = 27–33%); an effect that was reduced by the cyclooxygenase‐2 inhibitor bromfenac, and by HOE‐140. FR‐190997 also induced pro‐matrix metalloproteinase (MMP)‐1 and MMP‐3 release from h‐CM cells. FR‐190997 significantly lowered IOP (37% [P < 0.001] with 30 μg, 24 h post‐topical ocular dosing) in ocular hypertensive eyes of conscious Cynomolgus monkeys. This effect was reduced by bromfenac and completely blocked by a B2‐antagonist. FR‐190997 primarily stimulated uveoslceral outflow (UVSO) of aqueous humor (2.6 to 3.9‐fold above baseline). In conclusion, FR‐190997 is a B2‐receptor selective partial agonist that activates phospholipase C, mobilizes [Ca2+]; induces PG and pro‐MMP production, and that profoundly lowers IOP by promoting UVSO in ocular hypertensive Cynomolgus monkey eyes.